ANALISIS PENGARUH BUDAYA ORGANISASI DAN SISTEM PENGENDALIAN INTERNAL TERHADAP PENDETEKSIAN DAN PENCEGAHAN FRAUD - Agung Priyanto; Titik Aryati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
This research is to be able to know and to obtain empirical evidence analysis of the influence of organizational culture and internal control systems for the detection and prevention of fraud in a company. In this study population was Internal Auditor who works in 4 (four) companies in Indonesia which is chosen by random method (simple random sampling). The results of this study are significant influence between organizational culture and internal control systems to the dependent variable detection and prevention of fraud in the company or organization. This shows that jointly (simultaneously) organizational culture and internal control systems can improve the detection and prevention offraud in a company or organization. However, despite the partial internal control system has significant influence on the detection and prevention offraud is not the case with testing on organizational culture variable partially has no significant effect on the variable detection and prevention of fraud in the company or organization.